Treatments for chronic pruritus outside of the box. Issue 12 (13th August 2019) - Metz, Martin
Abstract: Patients with chronic pruritus are in desperate need of novel treatment options, as current therapeutic possibilities are often not effective, have a poor level of evidence and are mostly off‐label. In recent years, much effort has been put into the identification of potential targets for the treatment of chronic pruritus. More importantly, a number of promising new drugs that are aimed at treating pruritus in different conditions are currently in advanced stages of clinical trials. Here, current pharmacological developments leading to potential new drugs for the treatment of chronic pruritus within various conditions are summarized. Hopefully, these new approaches will result in effective and safe therapies for our patients with chronic pruritus associated with dermatological or non‐dermatological diseases in the near future.